2022
DOI: 10.2147/dddt.s339555
|View full text |Cite
|
Sign up to set email alerts
|

Research Progress in the Pharmacological Activities, Toxicities, and Pharmacokinetics of Sophoridine and Its Derivatives

Abstract: Sophoridine is a natural quinolizidine alkaloid and a bioactive ingredient that can be isolated and identified from certain herbs, including Sophora flavescens Alt, Sophora alopecuroides L , and Sophora viciifolia Hance . In recent years, this quinolizidine alkaloid has gained widespread attention because of its unique structure and minimal side effects. Modern pharmacological investigations have uncovered sophoridine’s multiple wide range biological activities, su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 83 publications
(138 reference statements)
0
6
0
Order By: Relevance
“…Its main component, Sophora flavescens, has many effects, including antibacterial and anti-inflammatory, insecticidal and anti-pruritic, anti-viral, and analgesic (He et al, 2015). Many studies have confirmed that the pharmacological mechanism of sophora flavescens may be via the activation or suppression of key molecules in certain cellular signaling pathways, such as nuclear factor kappa B (NF-kB), phosphatidylinositol 3-kinase/protein kinase B/mammalian target of rapamycin (PI3K/AKT/mTOR) and transforming growth factor-b/mothers against decapentaplegic homolog (TGF-b/Smad) (Lin et al, 2022;Tang et al, 2022). Furthermore, other herbs in the formula also have certain bactericidal and antiinflammatory effects, which complement each other.…”
Section: Discussionmentioning
confidence: 99%
“…Its main component, Sophora flavescens, has many effects, including antibacterial and anti-inflammatory, insecticidal and anti-pruritic, anti-viral, and analgesic (He et al, 2015). Many studies have confirmed that the pharmacological mechanism of sophora flavescens may be via the activation or suppression of key molecules in certain cellular signaling pathways, such as nuclear factor kappa B (NF-kB), phosphatidylinositol 3-kinase/protein kinase B/mammalian target of rapamycin (PI3K/AKT/mTOR) and transforming growth factor-b/mothers against decapentaplegic homolog (TGF-b/Smad) (Lin et al, 2022;Tang et al, 2022). Furthermore, other herbs in the formula also have certain bactericidal and antiinflammatory effects, which complement each other.…”
Section: Discussionmentioning
confidence: 99%
“…Another quinolizidine alkaloid is sophoridine, which is found in many traditional Chinese plants such as S. davidi var. davidi, S. japonica L., S. flavescens Alt., and S. alopecuroides L. (Tang et al, 2022). It showed various pharmacological actions such as anticancer, hepatoprotective, myocardial protective, antiviral, and anti-inflammatory effects (Wang et al, 2022).…”
Section: In Vitromentioning
confidence: 99%
“…Sophoridine, known as 5β-matrine, is a quinolizidine-based alkaloid that is present in many traditional Chinese herbs and possesses antitumor, anti-inflammatory, antiviral, and myocardial protective activities. These pharmacological properties indicate that sophoridine has a potential value in the prevention and treatment of these diseases. Sophoridine hydrochloride injection was approved by the State Food and Drug Administration (SFDA, China) as an antitumor drug in 2005 (H2005ll3l, 30). In recent years, a series of structure modifications have been conducted to improve its anticancer properties, and the design strategy mainly focuses on the N-16 position and C-14 position of the lactam ring or opening the lactam ring. , However, its anti-inflammatory activity is far from satisfactory (Table ), and related structural modification is extremely limited.…”
Section: Introductionmentioning
confidence: 99%